Tantangan Pembelajaran Hybrid di Perguruan Tinggi - Akhmad Asyari; Muhamad Ahyar Rasidi (ISLAMIKA, 2022)
The transmission of Covid 19 urges all countries in the world to carry out universal transformations in various fields including education. This study aims to describe the design and challenges in hybrid learning. This research is a literature study research that is analyzing various relevant literatures with the research focus. The results of the study illustrate that hybrid learning is carried out by utilizing various applications such as LMS and google classroom coupled with limited face-to-face learning. Some of the challenges in implementing hybrid learning include being faced by lecturers and students, for lecturers to add to their work such as digitizing learning materials and disseminating them through various social media features that are accessible to students, and developing learning tools. Another challenge is the difficulty in motivating students. The challenges for students include low learning motivation, low internet access availability, and not being able to work in groups because of the rules for crowding and wearing masks and maintaining health protocols.